2002
DOI: 10.1111/j.1348-0421.2002.tb02724.x
|View full text |Cite
|
Sign up to set email alerts
|

Additional Inhibitory Effect of Tea Extract on the Growth of Influenza A and B Viruses in MDCK Cells

Abstract: It has been previously reported that green-tea extract (GTE) inhibits the growth of influenza virus by preventing its adsorption. In this study, we further investigated whether GTE exerts an additional inhibitory effect on the acidification of intracellular compartments such as endosomes and lysosomes (referred to as ELS) and thereby inhibits the growth of influenza A and B viruses in Madin-Darby canine kidney cells. The vital fluorescence microscopic study showed that GTE inhibited acidification of ELS in a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 10 publications
0
66
0
Order By: Relevance
“…Anti-Flu drugs have been developed by many researchers, but they are problematic because the drugs cause side effects, and viruses tolerant to the drugs appear. It has been observed that BTE and GRTE have antiFlu functions (Imanishi et al, 2002;Clark et al, 1998;Nakayama et al, 1993;Song et al, 2005;Weber et al, 2003). However the anti-Flu function of Goishi tea has not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Anti-Flu drugs have been developed by many researchers, but they are problematic because the drugs cause side effects, and viruses tolerant to the drugs appear. It has been observed that BTE and GRTE have antiFlu functions (Imanishi et al, 2002;Clark et al, 1998;Nakayama et al, 1993;Song et al, 2005;Weber et al, 2003). However the anti-Flu function of Goishi tea has not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…Flu multiplies through four infecting steps: adsorption, invasion of target cells, replication of viral genome in the cells, and release from the cells (Imanishi et al, 2002;Nakayama et al, 1993;Sidwell et al, 2000;Song et al, 2005). Therefore, we tested which steps GTE inhibited.…”
Section: Effects Of Gte On Cytopathy Of Mdck Cells By Pr8mentioning
confidence: 99%
See 2 more Smart Citations
“…Ehrhardt et al [9] reported the extract of special variant of the Mediterranean plant Cistus incanus, CYSTUS052 interferes with the virus surface proteins and inhibits binding of the virus particle to cellular receptors. Also Imanishi et al [17] suggested that catechins interfere with the virus-cell membrane fusion by inhibition of acidification of endosome. The efficacy of the MOEO ingredient on the cell surface proteins such as, oligosaccharides or sialic acids (SA) that are receptors for influenza viruses, was not described until now.…”
Section: Discussionmentioning
confidence: 99%